Water Distribution in a Fire Protection System (Case Study Of DKK Semarang Building Simulation by Epanet 2.0) - Nurhakim, Yanuar Ali; Utomo, Karuniadi Satrijo (Jurnal Teknik Sipil dan Perencanaan, 2021)
Abstract Fire is a disaster that must be avoided in various ways, one of them is by using a fire extinguishing system to prevent fire disaster. This study used the Semarang City Health Office (DKK) Building as a sample. The purposes of this research were; (1) to find out whether the application of the fire protection system at DKK Building has met the regulations and (2) to determine whether the water distribution in the fire protection system in the Semarang DKK Building is functioning properly as needed. Data collection methods in this study consisted of observation and literature study. The observation was used to find research data in the form of planning drawings on the building protection system and the literature study was carried out to obtain data in the form of standard tool specifications and rules for using tools in the protection system. This study also used an analysis method based on an application program called Epanet 2.0. The Epanet program was used to simulate a hydraulic model according to the fire protection system at DKK Building. The results of the analysis using the Epanet 2.0 show that the sprinkler system has met the needs based on the amount of water supply discharge and based on the required pressure. The underground tank volume of 150 m3 has met the requirements based on SNI 03-3989-2000. The pressure value for all sprinklers has met the requirements of SNI 03-3989-2000 with the smallest pressure value is 2.5 kgf / cm2. The sprinkler system does not meet the water distribution value set in NFPA 13 with a maximum distribution time of 50 seconds while the analysis results show that the distribution time is 205 seconds. The pressure value at all points of the fire hydrant system meets the SNI 03-1745-2000 rules with a maximum value not exceeding 24.1 bars. The pressure value at the farthest hydrant box hose connection does not meet the SNI 03-1745-2000 rules with the pressure value at the farthest hydrant box is 4.6 bars, where is the minimum pressure is 6.9 bars.